APLIKASI BUKU TAMU DAN PENILAIAN KINERJA PADA SEKSIPELAYANAN INFORMASI DAN RENCANA KOTA BIDANG DOKUMENTASI DAN PELAPORAN: Studi Kasus: Dinas Tata Ruang Dan Cipta Karya Kota Bandung - Rini Nuraini Sukmana; Dina Rostiana; Dani Pradana Kartaputra (LPPM STMIK Bandung, 2020)
The process of charging the Guest Book is still done manually and are not computerized and report guest book is still a simple report on the Section of Information Services and Town Planning Sector Documentation and Reporting Department of Spatial Planning and Bandung Human Settlement, making data retrieval guest information and preparing reports Guest Book takes a long time and the service process could not predict the success or failure of the service rendered. It required an application system that can support the needs of the process of charging the Guest Book and performance assessment of service personnel who can facilitate care workers in search of information guest data and as an evaluation of service personnel in order to serve the community for the better again, and can produce information in the form report to be used by staff, Head of Section, Head of Division and Head of Department, become faster and help solve the problems faced.